2007
DOI: 10.1021/cm7029344
|View full text |Cite
|
Sign up to set email alerts
|

Self-Templated Synthesis of Nanoporous CdS Nanostructures for Highly Efficient Photocatalytic Hydrogen Production under Visible Light

Abstract: Nanoporous CdS nanostructures, including nanosheets and hollow nanorods, have been prepared by a two-step aqueous route, which consists of a first precipitation of nanoporous Cd(OH) 2 intermediates and a subsequent S 2-/OHion-exchange conversion of the obtained Cd(OH) 2 used as template either to nanoporous CdS nanosheets with sizes up to 60 nm and an average thickness of about 9 nm or to CdS hollow nanorods with lengths up to 30 nm and outer diameters in the range 7-14 nm. The obtained CdS nanostructures cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
662
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 950 publications
(697 citation statements)
references
References 61 publications
15
662
2
6
Order By: Relevance
“…Bao et al [18] realized a QE of about 60 per cent at 420 nm for H 2 evolution from Na 2 S/Na 2 SO 3 solution by loading 13 wt% of Pt on nanoporous CdS. The activity depends on the Pt-loading content, the amount of catalyst and the concentration of sacrificial regents, and was attributed to an efficient charge separation, a fast transport of the photogenerated carriers and a fast photochemical reaction at the CdS/electrolyte interface [18]. Subsequently, we reported a QE of 50 per cent at 420 nm for H 2 evolution from Na 2 S/Na 2 SO 3 solution on CdS synthesized by a hydrothermal method through loading less than 1 wt% of Pt [11].…”
Section: Results and Discussion (A) Noble Metals As Reduction Cocatalmentioning
confidence: 99%
See 1 more Smart Citation
“…Bao et al [18] realized a QE of about 60 per cent at 420 nm for H 2 evolution from Na 2 S/Na 2 SO 3 solution by loading 13 wt% of Pt on nanoporous CdS. The activity depends on the Pt-loading content, the amount of catalyst and the concentration of sacrificial regents, and was attributed to an efficient charge separation, a fast transport of the photogenerated carriers and a fast photochemical reaction at the CdS/electrolyte interface [18]. Subsequently, we reported a QE of 50 per cent at 420 nm for H 2 evolution from Na 2 S/Na 2 SO 3 solution on CdS synthesized by a hydrothermal method through loading less than 1 wt% of Pt [11].…”
Section: Results and Discussion (A) Noble Metals As Reduction Cocatalmentioning
confidence: 99%
“…A main shortcoming for CdS (and other sulfide or nitride semiconductors) photocatalyst is the photo-instability, which is owing to photocorrosion (CdS + 2h + → Cd 2+ + S) [18]. The reaction time courses (figure 5) for H 2 evolution showed that the rate of H 2 production over Pt/CdS gradually decreases and an evident drop in the activity is found after an irradiation for 7 h [11].…”
Section: (D) Dual Cocatalyst For Reduction and Oxidation Half Reactionsmentioning
confidence: 99%
“…4 Interest in the synthesis of colloidal semiconductorÀmetal hybrid nanostructures has grown exponentially in recent years. 1 33 Some of these reports build upon earlier work on the surface modification of microcrystalline semiconductors using platinum group metals as a way to generate hydrogen evolving photocatalysts, for example, CdSÀPt doped wth Zn and Ag sulfides, 34,35 and powders made of MS/CdS/M(M = Pt, Ir), 36…”
Section: ' Introductionmentioning
confidence: 99%
“…4 Interest in the synthesis of colloidal semiconductorÀmetal hybrid nanostructures has grown exponentially in recent years. 1 33 Some of these reports build upon earlier work on the surface modification of microcrystalline semiconductors using platinum group metals as a way to generate hydrogen evolving photocatalysts, for example, CdSÀPt doped wth Zn and Ag sulfides, 34,35 and powders made of MS/CdS/M(M = Pt, Ir), 36Received: May 27, 2011 Revised:June 27, 2011ABSTRACT: Reliable synthesis of semiconductorÀmetal heterostructures would increase their availability for fundamental studies and applications in catalytic, magnetic, and opto-electronic devices. Here, we demonstrate there are three main pathways for the formation of Pt and Pd nanoparticles on CdS and CdS 0.4 Se 0.6 nanorods.…”
mentioning
confidence: 99%
“…Hydrogen evolution stopped at the absorption edge in the tail region (>600 nm), revealing that the visible-light response of the photocatalyst is due to the band-gap transition between the valence and conduction bands. 198 The photocatalytic activity for the hydrogen evolution over CdS nanorods and nanowires has also been studied. [205][206][207][208] Fig.…”
mentioning
confidence: 99%